Вплив невизначеності вимірювань на оцінку відповідності медичних виробів - Кошева, Лариса Олександрівна; Оникієнко, Юрій Юрійович; Павлов, Євген Олександрович (НТУ "ХПІ", 2017)
Розглянуто вимоги міжнародних документів до оцінювання відповідності виробів встановленим вимогам до них з урахуванням невизначеності результатів, оцінюваної при випробуваннях. Розроблено методику оцінювання невизначеності результату при проведенні випробування на прикладі дитячого інкубатору для новонароджених. Показано, що для більшої вірогідності ухвалення рішення про відповідність необхідно аналізувати фактори впливу на невизначеність результату. Показані підходи для врахування оціненої невизначеності результатів вимірювань при оцінці відповідності. Показано, що для забезпечення встановлених ймовірностей ризиків та підвищення вірогідності прийняття рішення застосовують захисні смуги, довжина яких пов’язана із стандартною невизначеністю, а місце розташування – із характером помилкового рішення.

The requirements of international documents for assessing the conformity of products to their established requirements are considered, taking into account the uncertainty of the results evaluated during the tests. The method of estimating the uncertainty of the result during the test on the example of a child incubator for newborns is developed. It has been shown that in order to be more likely to decide on conformity, it is necessary to analyze the factors of influence on the uncertainty of the result and to consider only those that do not provide normal testing conditions and can significantly distort the real results. Approaches to take into account the estimated uncertainty of measurement results in the assessment of conformity are shown. For products of a regulated field, that includes medical products, the recommendations for the decision rule applying are based on the calculation of the probability of compliance and the probability of two types of false decisions based on the density of the probability distribution of valuesof the measured value, the limits of the tolerance interval and the acceptance interval. It is shown that in order to ensure the established risk probabilities and increase the probability of decision-making use guard band, the length of which is associated with standard uncertainty, and the location - with the nature of the false decision.
Influence of uncertainty measurements on evaluation of conformity for medical devices
Keywords: випробування; правило вирішальне; поле допуску; границі приймальні; смуга захисна; measurement; conformity assessment; test; decisive rule; tolerance interval; acceptance interval; guard band